2000
DOI: 10.1128/jvi.74.1.523-528.2000
|View full text |Cite
|
Sign up to set email alerts
|

Small Dense Nuclear Bodies Are the Site of Localization of Herpes Simplex Virus 1 U L 3 and U L 4 Proteins and of ICP22 Only When the Latter Protein Is Present

Abstract: The herpes simplex virus 1 U L 3 and U L 4 open reading frames are expressed late in infection and are not essential for viral replication in cultured cells in vitro. An earlier report showed that the U L 4 protein colocalizes with the products of the ␣22/U S 1.5 genes in small nuclear dense bodies. Here we report that the U L 3 protein also colocalized in these small nuclear dense bodies and the localization of U L 3 and U L 4 proteins in these bodies required the presence of ␣22/U S 1.5 genes. In cells infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 23 publications
2
24
0
Order By: Relevance
“…11). The nuclear localization of ICP22 was also characterized by expression in small, dense nuclear structures (14,30), whereas this pattern was observed in only a few VZV-infected cells during replication in melanoma cells.…”
Section: Downloaded Frommentioning
confidence: 99%
“…11). The nuclear localization of ICP22 was also characterized by expression in small, dense nuclear structures (14,30), whereas this pattern was observed in only a few VZV-infected cells during replication in melanoma cells.…”
Section: Downloaded Frommentioning
confidence: 99%
“…During later infection, ICP22 aggregates with UL3, UL4, and UL20.5 proteins as discrete, dense spots in the nucleus (11,18,27). However, deletion of ICP22 resulted in a decreased accumulation of UL3 and UL4, and neither UL3 nor UL4 localizes to…”
mentioning
confidence: 99%
“…However, deletion of ICP22 resulted in a decreased accumulation of UL3 and UL4, and neither UL3 nor UL4 localizes to the dense nuclear structures. Furthermore, ICP22 by itself is sufficient to form small, dense nuclear bodies in transfection assays without other viral proteins (18). Consequently, it was suggested that ICP22 may direct UL3 and UL4 to the dense nuclear structure (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Products of these latter genes are responsible for the posttranslational phosphorylation of ICP22 protein [41].In 2000, another complex formation was observed, called small dense nuclear bodies, which appear earlier than the RNAPII complex and contains ICP22, UL3, and UL4 [42]. ICP22 and UL13 mediate the phosphorylation of carboxyl terminal domain of RNAPII [43].…”
Section: Genestranscriptionmentioning
confidence: 99%